A review on 2D-ZnO nanostructure based biosensors: from materials to devices. Issue 2 (25th November 2022) - Krishna, M. Sankush; Singh, Sangeeta; Batool, Maria; Fahmy, Heba Mohamed; Seku, Kondaiah; Shalan, Ahmed Esmail; Lanceros-Mendez, Senentxu; Zafar, Muhammad Nadeem
Abstract : 2D ZnO nanostructure-based biosensors: synthesis, classification, types and applications. Abstract : During the COVID'19 outbreak, biosensing devices won increasing relevance, demonstrating their potential in the medical diagnostic field. Hence, the present review reports on the main advances in 2D-ZnO nanostructure-based biosensors. So far, bulk ZnO has shown potential for biosensing, optical, and power electronic applications, mainly based on its wide band gap. In the post graphene era, its 2-D allotropes like ZnO sheets and ZnO nanoribbons have outperformed the bulk ZnO structures for specific applications. ZnO demonstrates various stable and feasible morphologies: nanotubes, nanowires, nanorods, nanosheets, nanoparticles, and nanobelts. As a matrix layer in biosensing applications, ZnO strongly binds to biomolecules due to its high isoelectric point (IEP) and shows a strong sensitivity due to the high surface-to-volume ratio. Further, ZnO nanostructures used as a matrix layer play an important role in inhibiting specific biological interactions and hence improve the sensitivity of sensing devices. Further, bioselective layers are typically immobilized onto ZnO either by direct adsorption or by covalent binding. ZnO based biosensors are categorized into optical, piezoelectric, and electrochemical biosensors, among others, based on their biosensing mechanism. In particular, electrochemical sensors produce signals via an electrical pathway for detecting and monitoring the target molecules. Optical sensors produce signals based on luminescence or reflectance, among others. Piezoelectric biosensors produce signals by mass loading of the piezoelectric material. ZnO-based FET biosensors are also reported, showing sensing application by the change in the channel's conductance. Further, recent literature on the detection of COVID-19 using ZnO nanostructures is presented.